A consideration to natural frequencies under force control - Hideki SAKAI (Nihon Kikai Gakkai ronbunshu, 2015)
For characterizing vehicle dynamic behavior, the natural frequency and the damping ratio under position control, that is the control using steering angle as driver's input, have been developed as representative indices. However, a driver believes that he/she is controlling the vehicle maneuvers not only by steering angular input but also by steering torque input, that is, force control. Thus, in order to improve vehicle dynamic behavior further, it would be essential to carry out an analysis of the effect of force control on the natural frequencies and the damping ratios. However unlike position control, those indices under force control have been formulized only for neutral steer vehicles with a specific condition. The reason for this is that the characteristic equation of the system under force control consists of a combination of the steering system and the vehicle system, which turns into a biquadratic equation about Laplace operator s. To solve this equation, this paper formulized those indices by an approximation using general vehicle specifications, with final confirmation that the approximation errors do not exceed 5%. Finally, an example of an improvement in the vehicle dynamic behavior was demonstrated by comparing the results of original settings and those of assumed settings. Based on this result, it is shown that the vehicle dynamic behavior could be identified by force control indices as well as position control indices.